PERAN MASYARAKAT MENSUKSESKAN PEMUTAKHIRAN DATA PEMILIH DALAM PENYELENGGARAAN PILKADA 2024 DI DESA LELA KABUPATEN SAMBAS - Syahidin, Nelisa; Yuniarti, Desi; Amaluddin, Zainal (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2024)
ABSTRACT The current problem is that the community still has a minimal role in making Voter Data Updating for General Elections or Pilkada a success. Some of the problems that occur in Lela Village are the lack of public awareness and knowledge of the importance of updating voter data before the regional elections are held, the lack of public trust in the voter data updating officers (pantarlih). The focus of the problem in this research is: How is the Community's Role in Successfully Updating Voter Data Regarding the Implementation of Article 2 paragraph (8) PKPU Number 7 of 2024 concerning the Compilation of Voter Lists in the Implementation of Elections for Governor and Deputy Governor, Regent and Deputy Regent and Mayor and Deputy Mayor (Study in Lela Village, Teluk Keramat District) and Factors Inhibiting the Success of Updating Voter Data Regarding Article 2 paragraph (8) Concerning Preparation of Voter Lists in the Election of Governor and Deputy Governor, Regent and Deputy Regent, and Mayor and Deputy Mayor in Lela Village. This research uses empirical juridical research methods, namely reviewing statutory regulations and looking at the conditions of the facts found in the field regarding the Community's Role in Successfully Updating Voter Data in the Implementation of Article 2 paragraph (8) PKPU Number 7 of 2024 in Lela Village. To obtain data, researchers used interview and observation guidelines. Based on the research results, the community's role is very important in the process of updating voter data by inviting the community to play an active role by ensuring that their population data is recorded correctly and reporting any errors or changes to the data. This is in line with the General Election Commission Regulation Number 7 of data, and the inhibiting factors are the lack of awareness of the importance of updating data and the lack of public trust in election monitoring, lack of socialization to the public, as well as incomplete administrative problems.